The organization of knowledge in multinational firms - Anna Gumpert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Employees must learn about firm technologies to use them in production. Within multinational firms, knowledge can be acquired centrally, by managers at headquarters, or locally, by production workers. Local knowledge acquisition increases with the bilateral communication costs with central management, and decreases with local knowledge acquisition costs. This mechanism explains why multinationals foreign sales and their probability of entry decrease in the distance of a country from the multinationals home country, and why multinationals pay higher wages than comparable domestic firms. The selection into foreign destinations and the foreign productivity distribution of German multinationals are consistent with the models predictions.
Keywords: F21; F23; D21; 330